Về ước lượng Bayes của phương sai trong mô hình thống kês - Quang, Ung Ngọc (Journal of Computer Science and Cybernetics, 2016)
In the present note, we investigate the existence of Bayesian estimate for the variance component s2 in a nonlinear statistical model and the problem of finding an approach to this Bayesian estimate.